Akuntabilitas Berbasis Amanah dalam System Pelaporan Keuangan Syariah: Persfektif Akuntansi Islam - Andi Muh Nur Hidayat; Masyhuri, Masyhuri (Journal of Economic and Business Advancement, 2026)
This study examines accountability based on the concept of amanah within the Islamic financial reporting system from the perspective of Islamic accounting. Islamic financial reporting is not merely a technical process of presenting financial information, but represents a form of moral and spiritual responsibility rooted in Islamic values. The concept of amanah emphasizes honesty, justice, and transparency as core principles that guide the preparation and disclosure of financial reports. Using a qualitative and conceptual approach, this research analyzes classical Islamic thought, contemporary Islamic accounting literature, and established standards issued by regulatory and international institutions. The findings indicate that accountability in Islamic financial reporting extends beyond compliance with accounting standards and encompasses responsibility to Allah, society, and all stakeholders. The integration of maqasid al-shariah into financial reporting practices enhances the ethical quality and credibility of Islamic financial institutions. Strengthening accountability based on amanah requires consistent implementation of Islamic values, effective governance mechanisms, and continuous ethical awareness among accounting practitioners to ensure sustainable and trustworthy Islamic financial reporting.